2009
DOI: 10.1111/j.1551-2916.2009.03313.x
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Piezoelectric Properties in Mn‐Modified (1−x)BiFeO3xBaTiO3 Ceramics

Abstract: In the current work, the bulk (1−x)BiFeO3–xBaTiO3 system has been studied as a potential lead‐free piezoelectric material. Barium titanate (BaTiO3) in solid solution with bismuth ferrite (BiFeO3) is observed to stabilize the perovskite structure and improve switching behavior. Samples with various content of BaTiO3 were prepared via solid‐state route, and pure perovskite phase was confirmed by X‐ray diffraction. Modification of the BaTiO3–BiFeO3 material with Mn improved DC resistivity by one to five orders of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
300
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(327 citation statements)
references
References 20 publications
19
300
3
5
Order By: Relevance
“…The measured maximum d 33 (124 pC N À1 ) of BT-0.725BFO for our samples is quite promising compared with the reported d 33 (116 pC N À1 ) for Mn-doped BT-0.75BFO. 28 The measured d 33 (54 pC N À1 ) of BT-0.75BFO is also comparable with the reported d 33 (47 pC N À1 ) of BT-0.75BFO. 28 Systematic measurement of d 33 as a function of composition in our study led to the identification of BT-0.725BFO composition that provides the best performance.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The measured maximum d 33 (124 pC N À1 ) of BT-0.725BFO for our samples is quite promising compared with the reported d 33 (116 pC N À1 ) for Mn-doped BT-0.75BFO. 28 The measured d 33 (54 pC N À1 ) of BT-0.75BFO is also comparable with the reported d 33 (47 pC N À1 ) of BT-0.75BFO. 28 Systematic measurement of d 33 as a function of composition in our study led to the identification of BT-0.725BFO composition that provides the best performance.…”
Section: Resultssupporting
confidence: 75%
“…28 The measured d 33 (54 pC N À1 ) of BT-0.75BFO is also comparable with the reported d 33 (47 pC N À1 ) of BT-0.75BFO. 28 Systematic measurement of d 33 as a function of composition in our study led to the identification of BT-0.725BFO composition that provides the best performance. There was no ME response in the BT-0.025BFO due to its small magnetic properties given by low content of Fe ions even though it exhibited good piezoelectric values (g 33 ¼ 10.5 Â 10 mV m N À1 and d 33 ¼ 78 pC N À1 ).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…9) Since then, a number of studies 10)15) have demonstrated the impressive properties, both electrical and electromechanical, that can be obtained from this family of materials, often without any additional compensatory doping and/ or process optimization. One of the more intriguing aspects of these systems (and one that is often noted in casual conversations among researchers working on these materials, but not often reported in modern literature) is how resilient they appear to be to relatively large changes in processing parameters that would, in many other electroceramic systems, result in dramatic changes in electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Owing to its rhombohedral structure, the ferrite has been considered as an end-member of a variety of leadfree solid solutions exhibiting morphotropic phase boundary (MPB), which is believed to be the key for obtaining high piezoelectric properties. Some recently studied systems are BiFeO 3 -REFeO 3 (RE = La, Nd, Sm, Gd, Dy), [4][5][6] BiFeO 3 -BaTiO 3 , 7,8 and BiFeO 3 -Bi(Zn 0.5 Ti 0.5 )O 3 . 9 In addition, the high T C of BiFeO 3 enables to design MPB compositions suitable for high-temperature piezoelectric applications, such as the recently emerged BiFeO 3 -PbTiO 3 .…”
Section: Introductionmentioning
confidence: 99%